On Certain Approaches to Development of Foreign Language Professionally-Oriented Textbook for Engineering Bachelor Courses - E. V. Rybakova (Научный диалог)
The article is devoted to the development of professionally-oriented textbooks to the engineering bachelor courses. Stages of development of the concept of professionally-oriented textbooks are considered from the standpoint of realization of communicative approach in teaching professional foreign language. Considerable attention is paid to defining the thematic professional content of textbook sections, to ensuring its conformity with modern educational standards. The need for problem consideration of professional themes is emphasized as a way of stimulating communicative activities. Types of discourse are specified within which intercultural professional communication between bachelors of engineering profile should be implemented. Special attention is paid to the development of exercise materials based on authentic texts, representing the functional and stylistic characteristics of key types of discourse and developing bachelors’ ability to use different discourse strategies. Novelty of research consists in the fact that it considers the possibility of modelling professional activity in the textbook by constructing professional subject for each thematic section, which would determine logically interconnected sequence of situations of oral and written professional interaction that involves interpretation and generation of typical texts representing the business, professional, and scientific discourse. It is noted that the communicative focus of the textbook is provided through the development of exercises based on authentic texts relevant to the list of identified typical communicative situations.